Analog circuit topology synthesis by means of evolutionary computation. (April 2019) - Rojec, Žiga; Bűrmen, Árpád; Fajfar, Iztok
Abstract: Designing an analog electrical circuit requires substantial effort and time by a highly-skilled designer. Many tools have been devised to aid engineers in the design procedure, from simulators to parameter optimization tools, which largely assist in fine-tuning the parameter values of circuits with predetermined topologies. In this paper, we propose a new approach to circuit optimization that is capable of searching not only for the parameter but also the topological space. Starting from a high-level statement describing a desired circuit functionality, the proposed method can either improve a given circuit, or create a novel topology with given resources, based on the Darwinian theory of evolutionary selection. Our method uses a global parameter optimization method PSADE to speed up evolutionary convergence. We use the proposed algorithm (both single- and multi-objective) to successfully evolve passive, active, and BiCMOS circuits.